Critical Anatomic Variants in Peripheral Artery Disease Interventions - Ince, Okan; Tran, Patrick; Arslan, Bulent (Seminars in Interventional Radiology, 2025)
Variant anatomy is relatively common in the lower extremity arteries and can play a role both in the incidence of peripheral arterial disease and the interventions performed to treat such disorders. Recognition of such anatomic variants prior to performing interventions on these patients is vital to be able to appropriately plan arterial approaches and in determining what intervention may be most appropriate for such patients. Interventional radiologists who perform lower extremity arterial interventions should be familiar with the most common anomalies affecting these vessels; this article discusses common lower extremity arterial anomalies and how these anomalies can affect interventional procedures in these vascular distributions.
Keywords: peripheral arterial disease; anatomy; interventional radiology; lower extremity; variant